An Unedited Manuscript of Giacomo Leopardi “Sopra la riputazione di Q. Orazio Flacco presso gli antichi” - Capuzza, Vittorio (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
In 2020, the author of this article found an unpublished manuscript by Giacomo Leopardi among the papers of the National Library of Naples. The title of the autograph does not correspond to the content expressed by the young Leopardi: this opens up several scenarios and parallel hypotheses, which will be discussed and further explored here.